2021
DOI: 10.1111/ejn.15406
|View full text |Cite
|
Sign up to set email alerts
|

Leukoaraiosis and acute ischemic stroke

Abstract: Ischaemic stroke is characterized by high morbidity, high disability rate, high mortality and high recurrence rate, which can have a grave impact on the quality of life of the patients and consequently becomes an economic burden on their families and society. With the developments in imaging technology in recent years, patients with acute cerebral infarction are predominantly more likely to be diagnosed with leukoaraiosis (LA). LA is a common degenerative disease of the nervous system, which is related to cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 97 publications
0
5
0
Order By: Relevance
“…White matter hyperintensities (WMH), also called white matter lesions or leukoaraiosis, are frequently seen as hyperintense areas on T2-weighted brain MRI of predominantly elderly people ( Manolio et al, 1994 ; for a review, see Tang et al, 2021 ). While not fully understood, both vascular and non-vascular causes are involved ( Schmidt et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…White matter hyperintensities (WMH), also called white matter lesions or leukoaraiosis, are frequently seen as hyperintense areas on T2-weighted brain MRI of predominantly elderly people ( Manolio et al, 1994 ; for a review, see Tang et al, 2021 ). While not fully understood, both vascular and non-vascular causes are involved ( Schmidt et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Early research primarily centered on the intimate link between LA and vascular health, especially its connection to cerebral small vessel disease (CSVD) [26][27][28]. Multiple clinical studies have robustly established a signi cant correlation between LA and lacunar infarctions [29], hemorrhagic strokes [30,31], and ischemic strokes [5,32]. Some investigations have suggested that individuals with severe LA face twice the risk of stroke compared to the general population [5,33].…”
Section: Discussionmentioning
confidence: 99%
“…Small vessel disease-related WMHs are associated with pathologies of the vascular structures including small arteries, arterioles, capillaries, small veins, venules, and the glymphatic system. [13][14][15][16] Possible mechanisms of these vascular pathologies include arterial stiffness, vascular oxidative stress, chronic hypoxia, vascular endothelial cell damage, blood-brain barrier dysfunction, inflammation, demyelination, axonal cleavage, gliosis, and brain connectivity destruction. [13][14][15][16][17] Earlier data suggested different vasculogenic mechanisms in deep versus PVWMH.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] Possible mechanisms of these vascular pathologies include arterial stiffness, vascular oxidative stress, chronic hypoxia, vascular endothelial cell damage, blood-brain barrier dysfunction, inflammation, demyelination, axonal cleavage, gliosis, and brain connectivity destruction. [13][14][15][16][17] Earlier data suggested different vasculogenic mechanisms in deep versus PVWMH. 18 Destruction of endothelium and interstitial edema (by accumulation of interstitial fluid around the ventricle by preventing its reabsorption due to venous occlusion) seems to play a crucial role in PVWMH.…”
Section: Discussionmentioning
confidence: 99%